Accessing the proteome of extracellular vesicles via rapid acoustic isolation of a minute human blood plasma sample - Havers, Megan ; 0000-0001-5014-8984; Scott, Aaron M.; Ortenlöf, Niklas; Welinder, Charlotte; Ekström, Simon; Baasch, Thierry; Evander, Mikael; Lenshof, Andreas ; 0000-0003-2887-6365; Gram, Magnus ; 0000-0002-5880-2925; Laurell, Thomas (Analytica Chimica Acta, 2025)
Background: Despite substantial progress in the field of mass spectrometry, there remain barriers to measuring the extracellular vesicles (EVs) proteome in blood plasma. Recent work has shown that isolating EVs can make it possible to detect proteins that have low abundance in plasma. Commonly used EV isolation methods either require large sample volumes and long ultracentrifugation times, or else result in population bias via targeted isolation. There is a great need for fast and easy methods to isolate EVs from small volumes of plasma, <10 μL, enabling biomarker discovery, e.g. in biobanked samples, where mass spectrometry can play an important role. Results: We unveil the extracellular vesicle proteome by using seed particle enhanced acoustic trapping to purify EVs from minute blood plasma samples (8 μL) in 6 min per sample. The differential mass spectrometry results find proteins which are significantly enriched (FDR-adjusted p-values<0.05) in acoustically trapped samples compared to raw (unprocessed) plasma, more than two thirds of those proteins have been associated with EVs previously. Additionally, we are able to increase the depth of analysis by detecting 51 low abundance proteins not detected in raw plasma, half of which are tagged with the gene ontology (GO) tag “extracellular exosome” (GO:0070062). Finally, we validate the novel use of neutrally charged silica seed particles paired with a washing flowrate of 200 μL/min, enabling the processing time to be halved and finding the same proteome as for tried-and-tested polystyrene seed particles with washing at 30 μL/min. Significance: Our microfluidics-based approach to EV isolation enables rapid processing of an individual minute blood plasma sample, demonstrating that personal proteomic information associated with EVs can be detected when acoustic trapping is used as a pre-processing step. By applying this technique to plasma from patient cohorts or mouse models, future studies may offer new insights into the role of EVs in the progression of diseases and reveal new diagnostic targets in the proteomic cargo of EVs.
Keywords: Acoustic trapping; Extracellular vesicles; Mass spectrometry; Microfluidics; Plasma; Proteomics